Analyzing the multi objective analytical aspects of distribution systems with multiple multi-type compensators using modified cuckoo search algorithm. Issue 6 (2nd November 2017) - Giridhar, Munigoti S.; Sivanagaraju, S.; Suresh, Chintalapudi V.; Umapathi Reddy, P.
Abstract: This paper presents a two stage solution strategy to solve multi objective optimization problem in the presence of capacitors, distributed generators (DGs) and automatic voltage regulators (AVRs) for better planning and operation of a primary distribution system. Using this, the economical aspects such as net savings and the technical aspects such as voltage deviation and section current index objectives are optimized while satisfying system equality and in-equality constraints. The optimum number of compensating devices and their optimal locations are identified in a given system so as to enhance the system security by minimizing the system power losses. The proposed methodology of finding the optimal sizes of compensating devices with multi-objective functions uses fuzzy decision approach to select the best compromised solution from the total generation Pareto solution as per the operators' requirement. The feasibility and effectiveness of the proposed method are examined on standard 15-node, 33-node and 69-node test systems. According to the analytical results, the proposed framework in the presence of compensating devices enhances the system performance more effectively. Graphical Abstract: Multi-objective optimal placement of multiple compensators